PELATIHAN CARA PENGOLAHAN PANGAN YANG BAIK (CPPB) BAGI PENGRAJIN TEMPE DESA MLIRIP MENUJU KEAMANAN PANGAN - Wulandari, Lusi Mei Cahya; Widari, Nyoman Sri; Sumewang, Filippo (Abdi Panca Marga, 2024)
Good Manufacturing Practises or Cara Pengolahan Pangan yang Baik (CPPB) are a prerequisite for producing safe, suitable, and high-quality processed food products. Despite being a flagship food in Mlirip Village, Mojokerto, tempe is still processed traditionally and does not meet the CPPB criteria. Community engagement aims to map and raise awareness about CPPB among tempe artisans in Mlirip Village. Mapping involves observing and interviewing seven tempe artisans, focusing on final product aspects, packaging, labeling, product information, documentation, and record-keeping. The mapping results revealed a 40% discrepancy in the final product and a 100% discrepancy in labeling and product information. Consequently, a CPPB socialization program conducted by Rumah Tempe Indonesia was based on these findings. The socialization efforts aimed to emphasize the importance of consistent quality in tempe products and the necessity of providing accurate labels and product information for the produced tempe. References Alvina, A., & Hamdani, D. H. (2019). Proses Pembuatan Tempe Tradisional. Jurnal Ilmiah Pangan Halal, 1(1), 9-11. Emilda, E., Wulandari, T., & Lazuarni, S. (2022). Pendampingan UMKM Penjual Jamu Dalam Meningkatkan Penjualan Melalui Kemasan, Merek, dan Label. Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 5(1), 53–60. https://doi.org/10.33330/jurdimas.v5i1.1249 Franklyn Purba, D., Nuraida, L., & Sutrisno Koswara, dan. (n.d.). Effectiveness Assessment of Food Quality and Safety Inspection Program for Household Food Industry (HFI) in Cianjur District. Jurnal Standardisasi 16(2), 103-112 Hanidah, I.-I., Mulyono, A. T., Andoyo, R., Mardawati, E., & Huda, S. (2018). Penerapan Good Manufacturing Practices Sebagai Upaya Peningkatan Kualitas Produk Olahan Pesisir Eretan-Indramayu AGRICORE: Jurnal Agribisnis dan Sosial Ekonomi Pertanian 3 (1), 359-426. Wulandari, LMC., Patrick, J., Pical, A., & Fortunatus, Y. (2023). Pemberdayaan Pengrajin Tempe Dusun Clangap Mojokerto Menuju UMKM Pangan Berdayasaing Melalui Pembuatan Rak Tempe Dan Pelatihan Penyusunan SOP. Selaparang 7(1), 579-582. Putri, A. A., Rohmah, M., Emmawati, A., Andriyani, Y., & Rahmadi, A. (2023). Penerapan CPPB-IRT dan sistem jaminan produk halal sebagai upaya peningkatan mutu dan kehalalan produk UMKM. Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 6(2), 373–391. https://doi.org/10.33474/jipemas.v6i2.19633